Policy over practice: A review of groundwater governance research in Sub-Saharan Africa - Bont, Chris de; Börjeson, Lowe (Ubiquity Press, Ltd., 2024)
Groundwater is increasingly seen as crucial to both agricultural and domestic water supply in sub-Saharan Africa. Citing climate change and growing populations, there is especially a notable shift towards promoting groundwater for irrigation to ensure food security. Increased use of the resource will undoubtedly be accompanied with new questions of governance, with groundwater overexploitation in other parts of the world functioning as a strong cautionary tale. This article provides an overview of the current groundwater governance literature on sub-Saharan Africa. Using a critical water governance lens we analyse how groundwater governance is framed, what terms, categories, and measurements are used to describe and assess groundwater governance, and whose perspectives are considered. We also assess whether groundwater governance research has taken place across sub-Saharan African countries in a balanced way. We find that groundwater governance research in sub-Saharan Africa, even more so than elsewhere, ignores the voices and perspectives of those physically encountering the resource. Instead, it is dominated by the views of formal, technical groundwater experts focusing on the need for more hydrogeological data and formal policies. While the existing contributions to the literature are valuable, the current bias in perspectives calls for others to join the field of groundwater governance and to supplement current conceptualisations and approaches with those of users and others dealing with groundwater management on a daily basis. We argue that groundwater users’ practical governance experiences, locally adapted solutions and knowledges, can add important complementary perspectives and insights towards crafting effective, sustainable and equitable groundwater governance processes across the continent.